Symposium on Interactive 3D Graphics and Games 2011
DOI: 10.1145/1944745.1944772
|View full text |Cite
|
Sign up to set email alerts
|

GPU curvature estimation on deformable meshes

Abstract: Figure 1: On the left is one frame of an elephant animation visualizing estimated curvature. Blue indicates concave areas, red indicates convex areas, and green indicates saddle-shape areas. The middle is using surface curvature to approximate ambient occlusion. On the right is an orange volume with ∼1.5 billion vertices with Lambertian shading and ambient occlusion which we estimate curvature on in 39.3 ms. AbstractSurface curvature is used in a number of areas in computer graphics, including texture synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…It has already been shown that screen space estimation is easy to implement in computer games on current graphics hardware. Wesley et al (Griffin et al, 2011) introduced real time curvature estimation in the world space. They employed a programmable geometry shader to detect the normal curvature by analyzing the normal and position vectors of neighboring polygons.…”
Section: Methodsmentioning
confidence: 99%
“…It has already been shown that screen space estimation is easy to implement in computer games on current graphics hardware. Wesley et al (Griffin et al, 2011) introduced real time curvature estimation in the world space. They employed a programmable geometry shader to detect the normal curvature by analyzing the normal and position vectors of neighboring polygons.…”
Section: Methodsmentioning
confidence: 99%
“…This idea was extended in [20], where Guillaume et al apply this work to mesh based segmentation. However, these previous approaches either only applied to a single model [21] [2], or rely on the alignment of multiple scan-matches to highly accurate in order to build a single shape model for curvature estimation. Additionally, these previous approaches often assume relatively low-noise in the model, which is not the case when using low-cost depth sensors.…”
Section: Related Workmentioning
confidence: 99%
“…Most feature computation methods belongs to this category and thus operate on the CPU. GPU-based methods, have been proposed for the computation of specific features, like curvature (Griffin et al, 2011), but these methods do not generalize to the sampling of arbitrary neighborhoods. Screen space methods sample the geometric information of a mesh from a 2D pixel buffer, where each pixel encodes the projected surface position of the mesh from a specific point of view.…”
Section: Related Workmentioning
confidence: 99%
“…massively parallel stream processors, like commodity GPUs, at an arbitrary neighborhood scale. For these reasons, real-time computation is often limited to meshes with relatively low geometric complexity and 1-ring vertex neighborhoods (Griffin et al, 2011).…”
Section: Introductionmentioning
confidence: 99%